First-line Eradication of Helicobacter pylori Infection with High-Dose Amoxicillin and Vonoprazan: A Systematic Review and Meta-analysis - Yu, Hongxiu; Zhou, Zhengwen; Liu, Zhi (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Due to increasing Helicobacter pylori resistance, the effectiveness of proton pump inhibitor-based regimens has diminished. There is a need to assess the high-dose amoxicillin (≥3 g/day) and vonoprazan dual therapy through meta-analysis to deter mine if it is more effective than previous protocols. Materials and Methods: A computer search of PubMed, Web of Science, Cochrane Library, Embase, and ClinicalTrials.gov was carried out to identify randomized controlled trials of massive dose amoxicillin and vonoprazan double treatment for H. pylori infection, up to June 2023. The primary outcome measures were the eradication rate and adverse event rate. Results: A total of 7 studies encompassing 2601 patients were analyzed. The eradication rate of the high-dose dual group has no sta tistically significant differences compared to the control group (non-high-dose amoxicillin combined with vonoprazan) in intention-to treat (ITT) [OR=1.12, 95% CI (0.85, 1.48), P = .42] and per-protocol (PP) analysis [OR=1.08, 95% CI (0.74, 1.58), P = .69]. The incidence of adverse events [OR=0.63, 95% CI (0.45, 0.88), P = .007] was significantly reduced in the dual treatment group. Subgroup analysis revealed that the eradication rate in China [OR=1.34, 95% CI (1.01, 1.87), P = .04] was higher for the high-dose dual group compared with the control group in ITT analysis. Conclusion: The eradication rate of high-dose amoxicillin and vonoprazan dual regimen is similar to that of previous regimens, and the adverse event rate is significantly lower. Cite this article as: Yu H, Zhou Z, Liu Z. First-line eradication of helicobacter pylori infection with high-dose amoxicillin and vonoprazan: A systematic review and meta-analysis. Turk J Gastroenterol. 2025;36(7):410-419.